The CONSUMER SATISFACTION STUDY AT ALFAMART CIAWI: THE SIGNIFICANT ROLE OF RESPONSIVENESS AND LOCATION IN CONSUMER SATISFACTION - Hendi Sobari (Nusantara Journal Of Management Business (NUMABI), 2024)
This study aims to analyze the level of consumer satisfaction at Alfamart Ciawi and evaluate the significant role of two main factors, namely responsiveness and store location in determining consumer satisfaction. This research uses a survey method with a questionnaire distributed to a sample of consumers who shop at Alfamart Ciawi. Data collection was carried out by analyzing consumer perceptions of the responsiveness of services provided by Alfamart employees and store locations. The collected data is analyzed using statistical techniques such as regression to determine the relationship between the independent variables (responsiveness and location) and the dependent variable (consumer satisfaction). The research results show that responsiveness and store location have a significant influence on consumer satisfaction at Alfamart Ciawi. These findings provide valuable insight for Alfamart Ciawi management to improve service quality and pay attention to location factors to strengthen customer attraction.